2022
DOI: 10.17531/ein.2022.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis model as a planning tool for effective supply chains resistant to adverse events

Abstract: The article presents the problem of planning effective modular supply chains to resist adverse events. The lack of effective models for planning such supply chains based on the synergy of individual links widens the knowledge gap in this area. The analyses confirm the legitimacy of forming effective and reliable supply chains ready for fitting supplies to specific orders, adaptation to flexible and innovative transformations, and minimization of time losses and costs of restoring supply capacity in case of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 64 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Machine learning is also used to detect railway defects such as corrugation [ 18 ] which the performance was satisfying. Besides the mentioned literature, machine learning and mathematical models were used in different areas such as supply chain [ 19 ], railway design [ 20 ], inspection scheduling [ 21 ], and cost management [ 22 ]. The summary of related studies is shown in Table 3 .…”
Section: Exploration Of Track Geometry Measurement and Predictionmentioning
confidence: 99%
“…Machine learning is also used to detect railway defects such as corrugation [ 18 ] which the performance was satisfying. Besides the mentioned literature, machine learning and mathematical models were used in different areas such as supply chain [ 19 ], railway design [ 20 ], inspection scheduling [ 21 ], and cost management [ 22 ]. The summary of related studies is shown in Table 3 .…”
Section: Exploration Of Track Geometry Measurement and Predictionmentioning
confidence: 99%
“…The proper functioning of any construction company is often disturbed by the appearance of many decision-making problems, which certainly include difficulties related to the purchase and supply of materials and resources. The question of satisfying as much as possible the expectations of construction contractors with respect to suppliers of building materials has been addressed many times by researchers [1][2][3][4][5][6][7][8][9][10][11]. In literature, there are attempts to evaluate logistic systems by means of, among others, cost analyses and simulations, as well as multicriteria analysis of the impact of logistic system structure on inventory management.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Semenov and Jacyna [2] considered the problem of planning effective modular supply chains resistant to adverse events. Their analysis confirms the validity of forming efficient and reliable supply chains ready to match supplies to specific orders, adapt to flexible and innovative transformations, and minimize time losses and costs of restoring supply capacity in case of an emergency.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Finally, in Section 6, we present our concluding remarks. It is worth noting that in the more general setting of information modelling, being able to detect epidemic waves may help supply chains in planning increased resistance to such adverse events [28]. We note that all computations were carried out using the Matlab software package.…”
Section: Introductionmentioning
confidence: 99%